Mechanisms underlying acid tolerance in Lysinibacillus sp. ND7, a highly efficient nitrate degrader - Feifei Wang; Min Ai; Xiafei Yin; Lixue Liu; Hefei Shi; Guobin Liang (PLoS ONE, 2025)
In this study, the acid-tolerant strain Lysinibacillus sp. ND7 demonstrated excellent nitrate removal efficiency under acidic conditions, achieving a nitrate removal rate of 80.70 ± 0.02% in wastewater at pH 3.1. Metabolomics analysis revealed significant enrichment in pathways related to starch and sucrose metabolism, teichoic acid biosynthesis, and the phosphoenolpyruvate-dependent sugar phosphotransferase system (PTS). These pathways play a crucial role in providing energy, regulating metabolism, and maintaining cellular stability during nitrate degradation. Proteomic analysis showed a significant up-regulation of genes involved in the nitrate removal pathway. Additionally, the up-regulation of ABC transporter protein genes and the down-regulation of genes involved in oxidative phosphorylation and electron transport worked together to support the nitrate metabolic pathway and help the strain resist acid stress. In conclusion, these findings underscore the impressive nitrate removal capacity of the novel strain ND7 and offer new insights into the mechanisms through which ND7 resists acid stress under acidic conditions.